Audit Sistem Informasi Sumber Daya Manusia Pada Perusahaan Elektronika di Surabaya - Michelle Wong; Alexander Setiawan; Agustinus Noertjahyana (Jurnal Infra, 2018)
Electronic Company in Surabaya is a company whichengaged in the electronic sales with branches scattered insome big cities in Java Island. The labor needs are increasedand employement activities need to be integrated acrossbranches require coordination by human resourcesinformation system (HRIS). In order to know HRISmanagement process’ level with current needs, it is requiredto conduct process capability level measurement. COBIT 5 isa framework used to measure HRIS process capability leveland has been combined with ITIL V3 2011 to help audit’s datacollection.The following steps in this research start from literature studyto review business documents and literature study ofresearch’s material, then to conduct interview, observationand questionnaire on data collection and data management.The result of data management was used to assess capabilitylevel and gap analysis, before finally it was verified andpassed improvement strategies and process recommendations.As the result of process capability level measurement, serviceagreements management process at Electronic Company inSurabaya is on level 1 (performed process) and level 2(managed process).